the ENGARUH MANAJEMEN PEMBELAJARAN DAN SIKAP GURU TERHADAP TINGKAH LAKU SISWA KELAS VI - Wildaningrum, Delaga Tafrikhatul; Baedowi, Sunan; Agustini, Ferina (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
This research was motivated by many distorted student behaviors. Such as, damaging classroom facilities, students who often quarrel, commit acts of cheating, passive students. The problem in this study is how the influence of learning management and teacher attitudes on the behavior of class VI students. The purpose of this study is to determine learning management and teacher attitudes towards the behavior of grade VI students of SD Negeri 03 Karangtalok. Qualitative method with phenomenological type of research. With the number of students in class VI totaling 28 students, the sample taken was 5 students. This research data is through interviews, questionnaires, documentation. The results obtained are that the teacher only makes a lesson plan, the success of students reaches 75%, some students are late for school, teachers provide guidance every day, teachers coordinate classes, students are sleepy, damage school facilities. It can be concluded that the learning management and attitude of the teacher are already quite good